2014
DOI: 10.4414/smw.2014.13971
|View full text |Cite
|
Sign up to set email alerts
|

Osteoarticular infections in young children: what has changed over the last years?

Abstract: Osteoarticular infections remain a significant cause of morbidity worldwide in young children. They can have a devastating impact with a high rate of serious and long-lasting sequelae, especially on remaining growth. Depending on the localisation of infection, they manifest as osteomyelitis, septic arthritis, a combination of both (i.e., osteomyelitis with adjacent septic arthritis) or spondylodiscitis. Osteoarticular infections can be divided into three types according to the source of infection: haematogenou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0
13

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 97 publications
2
52
0
13
Order By: Relevance
“…It also reduces the intraarticular pressure of the joint, subsequently decreases the risk of complications such as AVN of the bone and permanent cartilage damage. [11,12] However, our study showed that the patients did not gain advantages from surgery. In the 48 joints who underwent follow-up, the total rate of recovery was 72.9%, there was no significant difference between the operative and the nonoperative group.…”
Section: Discussionmentioning
confidence: 54%
“…It also reduces the intraarticular pressure of the joint, subsequently decreases the risk of complications such as AVN of the bone and permanent cartilage damage. [11,12] However, our study showed that the patients did not gain advantages from surgery. In the 48 joints who underwent follow-up, the total rate of recovery was 72.9%, there was no significant difference between the operative and the nonoperative group.…”
Section: Discussionmentioning
confidence: 54%
“…El diagnóstico es difícil y suele retrasarse en la mayoría de los casos 1-3 debido a la baja frecuencia de la enfermedad y a su clínica variable e inespecífica [1][2][3][4] . En los menores de 6 meses las manifestaciones clínicas son las más graves y a menudo se asocia a septicemia o a múltiples focos de infección 3 .…”
Section: Discussionunclassified
“…Las pruebas de laboratorio son inespecíficas en la mayoría de los casos, tal y como señala Ceroni et al 4 . Pueden encontrarse elevadas o ser normales.…”
Section: Discussionunclassified
“…[46][47][48] About 60% of childhood spondylodiscitis occurs in children aged 6 months to 4 years, and most yield sterile biopsies or grow Kingella kingae. 34,49 Among patients older than 4 years, there is a greater risk for vertebral osteomyelitis, and the S. aureus is the predominant isolate. Gower's sign (pathognomonic of Duchenne muscular dystrophy) can be helpful leading to a diagnosis in young children (aged 3.3-8 years) with lumbar discitis, and it resolves upon appropriate therapy.…”
Section: Bacterial Discitismentioning
confidence: 99%
“…11,12,33 Invasive diagnostic procedures such as needle aspiration and biopsy have attendant procedural and anesthetic risks, and the indication for these are not firmly established at present. 34,49 Magnetic resonance imaging can facilitate early diagnosis of pediatric spinal infections. In infections of the spinal cord, MR generally reveals hyperintense T2 signals and expansion of the cord.…”
Section: Diagnostic Evaluationmentioning
confidence: 99%